Comprehensive Analysis of Business Catering Samarinda’s Business Feasibility to Assess Its Potential and Sustainability - Mauliahasmi, Siti; Arbaiyah, Arbaiyah; Alimi, Darren Kaleb; Surahman, Surahman; Wibowo, Rahmawati Idha (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the feasibility of a catering business in Samarinda by reviewing four main aspects, namely marketing, operations, legality, and finance. The background of this study is based on the increasing trend of culinary businesses in Indonesia that utilize digital marketing strategies as the main means of expanding their market reach. The research method uses a mixed method approach, namely qualitative and quantitative. The qualitative approach was used to analyze business strategies, operational activities, and the implementation of business legality, while the quantitative approach was applied to assess financial feasibility through the indicators of NPV, IRR, PP, and BEP. The results show that the business is feasible with a positive NPV of IDR 264,833, an IRR of 14.60%, a payback period of 2.3 years, and a BEP at 58% of production capacity. In addition to being financially feasible, this business has also fulfilled legal aspects through the establishment of the business entity and the ownership of an NIB and NPWP. This study emphasizes the importance of integrating digital marketing strategies with business feasibility analysis to create a competitive, innovative, and sustainable culinary business in the competitive digital era.